High-frequency percussive ventilation in acute respiratory failure - Andrea Bruni; Giuseppe Neri; Gianmaria Cammarota; Vincenzo Bosco; Eugenio Biamonte; Letizia Troisi; Annalisa Boscolo; Paolo Navalesi; Federico Longhini; Eugenio Garofalo (ERJ Open Research)
Introduction High-frequency percussive ventilation (HFPV) is a ventilation mode characterised by high-frequency breaths. This study investigated the impact of HFPV on gas exchange and clinical outcomes in acute respiratory failure (ARF) patients during spontaneous breathing, noninvasive ventilation (NIV) and invasive mechanical ventilation (iMV). Methods This systematic review included randomised and nonrandomised studies up to August 2023. Inclusion criteria focused on adult ARF patients, HFPV application, comparisons with other ventilation modes, and outcomes related to oxygenation and clinical parameters. A pooled data analysis was performed comparing HFPV with iMV concerning gas exchange, pulmonary infection and mortality. Results Of the 51 identified records, 29 met the inclusion criteria. HFPV was safely and effectively applied to ARF patients during spontaneous breathing or NIV, improving oxygenation. For patients who underwent iMV, HFPV significantly enhanced oxygenation and the arterial partial pressure of carbon dioxide, reduced pulmonary infection occurrence and improved survival. Barotrauma rates were not elevated with HFPV, and haemodynamic stability remained unaffected. HFPV was also utilised in patients undergoing extracorporeal membrane oxygenation, resulting in improved lung recruitment and oxygenation. Conclusion HFPV had favourable effects on physiological and certain clinical outcomes in ARF patients. However, the overall evidence quality remains weak, necessitating large-scale randomised controlled trials for definitive conclusions.